Trends in Prevalence of Dementia in French Farmers from Two Epidemiological Cohorts. Issue 2 (19th December 2016) - Pérès, Karine; Brayne, Carol; Matharan, Fanny; Grasset, Leslie; Helmer, Catherine; Letenneur, Luc; Foubert‐Samier, Alexandra; Baldi, Isabelle; Tison, François; Amieva, Hélène; Dartigues, Jean‐François
Abstract : Objectives: To determine the prevalence of dementia and cognitive impairment in older people across generations. Design: Two prospective cohort studies (Personnes Agées QUID (PAQUID), Aging Multidisciplinary Investigation (AMI)). Setting: Baseline data from two subsamples of older farmers in southwestern France. Participants: PAQUID (n = 595) and AMI (n = 906) participants aged 65 and older living at home at baseline (1988 PAQUID, 2008 AMI). Measurements: Two methods were used to diagnose dementia: a clinical consensus diagnosis and a computer‐assisted taxonomy approach (cognitive impairment with disability (CIWD)) using Mini‐Mental State Examination and instrumental activity of daily living scores. Crude and standardized prevalences (using PAQUID age‐sex structure) and 95% confidence intervals were calculated, and logistic regression was used to explore confounding. Results: The prevalence of consensus diagnosis of dementia was higher in AMI in 2008 than in PAQUID in 1988 (12.0% vs 5.7%, P < .001), whereas the reverse was observed for CIWD (14.8% vs 23.8%, P < .001), confirmed by logistic regressions (odds ratio (OR)AMI vs PAQUID = 2.50, 95% confidence interval (CI) = 1.52–4.12; ORAMI vs. PAQUID = 0.60, 95% CI = 0.42–0.87, respectively). Educational level increased and management of vascular risk factors improved over the study period, and health and living conditions improved globally. Conclusion: These findings suggest global cognitive and functional improvement in old farmers (the prevalence of CIWD decreased by 40% over 20 years) and simultaneously a marked change in the subjective boundary between dementia and nondementia according to clinicians.